Analysis of the Relationship Between UTAUT Factors and Behavioral Intention to Use Google Classroom among Vocational High School Teachers - Rhema Thamariska; Puspanda Hatta; Endar Suprih Wihidayat (Institute of Multidisciplinary Research and Community Service, 2026)
The implementation of competency-based learning in vocational high schools requires effective assessment and timely feedback to ensure that students achieve the competencies demanded by industry. However, assessment and feedback activities are still frequently conducted manually, resulting in administrative inefficiencies, delayed feedback, and difficulties in monitoring students’ learning progress. Google Classroom provides an integrated digital platform that can facilitate assessment management and feedback delivery; however, its successful implementation depends on teachers’ acceptance of the technology. Therefore, this study aimed to analyze the relationships between Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, and Behavioral Intention to use Google Classroom among vocational high school teachers. A quantitative descriptive-correlational research design was employed involving 98 teachers selected through purposive sampling from three vocational high schools in Surakarta, Indonesia. Data were collected using a questionnaire developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The collected data were analyzed using IBM SPSS Statistics Version 27, employing descriptive statistics, the Kolmogorov-Smirnov normality test, and Spearman's Rank correlation analysis. The results revealed that all UTAUT constructs had positive and statistically significant relationships with Behavioral Intention. Performance Expectancy showed the strongest relationship (rs = 0.694, p 0.001), followed by Social Influence (rs = 0.620, p 0.001), Facilitating Conditions (rs = 0.585, p 0.001), and Effort Expectancy (rs = 0.565, p 0.001). These findings indicate that teachers’ intention to use Google Classroom is primarily associated with perceived usefulness, followed by social support, facilitating resources, and perceived ease of use. The findings imply that vocational schools should strengthen teachers’ digital competencies, improve institutional support, and ensure adequate technological infrastructure to promote the sustainable implementation of Google Classroom for assessment and feedback activities. Keywords: Google Classroom, performance expectancy, effort expectancy, UTAUT, Vocational Education.